The endodermis, a tightly controlled barrier for nutrients. (October 2017) - Doblas, Verónica G; Geldner, Niko; Barberon, Marie
Highlights: The endodermal cell layer forms two barriers: Casparian strips and suberin lamellae. Casparian strips are forming an apoplastic barrier. Suberin lamellae block the uptake from the apoplast into suberized cells. Endodermal suberization is responsive to nutritional stress. The apoplastic integrity is checked through vasculature-derived peptides. Abstract : Plant roots acquire nutrients from the soil and transport them upwards to the aerial parts. To reach the central vasculature of the root, water and nutrients radially cross all external cell layers. The endodermis surrounds the vascular tissues and forms diffusion barriers. It thereby compartmentalizes the root and allows control of nutrient transport from the soil to the vasculature, as well as preventing backflow of nutrients from the stele. To achieve this role, endodermal cells undergo two specialized differentiations states consisting of deposition of two impermeable polymers in the cell wall: lignin, forming the Casparian strips, and suberin lamellae. Recent publications showed that endodermal barrier formation is not a hard-wired, irreversible process. Synthesis and degradation of suberin lamellae is highly regulated by plant hormones in response to nutrient stresses. Moreover, Casparian strip continuity seems to be constantly checked by two small peptides produced in the vasculature that diffuse into the apoplastic space in order to test endodermal barrier integrity. This review discusses the recent understanding of endodermal barrier surveillance and plasticity and its role in plant nutrition.